SOSIALISASI PEMBUATAN NIB KEPADA PELAKU UMKM DI DUSUN KALANGAN, CANDISARI, SECANG - Tri Nur Fadilah; Yeny Fitriyani; M Pudail (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
This activity is intended to provide an understanding of the importance of applying for a business license and introducing a Business Identification Number (NIB) to apply for a business license online. Business legality is a standard that business actors must meet. Micro, Small, and Medium Enterprises (MSME) must meet these requirements to compete in the free-market era. This demand is a problem because many business actors do not have business legality. Therefore, community service activities are needed in the form of assistance, especially for artisans and MSME, to develop their business in a better direction. The research method used is the PAR (Participatory Action Research) method. This study aims to provide knowledge and information on making NIB to business actors to develop their business. The community carried out the study results to understand and increase understanding about making NIB, which every business actor must own. Then simplify business operations because they have obtained business legality.